Cerebral oximetry: a developing tool for monitoring cerebral oxygenation during cardiopulmonary resuscitation. Issue 1 (15th November 2021) - Huppert, Elise L.; Parnia, Sam
Abstract: Despite improvements in cardiopulmonary resuscitation (CPR), survival and neurologic recovery after cardiac arrest remain very poor because of the impact of severe ischemia and subsequent reperfusion injury. As the likelihood of survival and favorable neurologic outcome decreases with increasing severity of ischemia during CPR, developing methods to measure the magnitude of ischemia during resuscitation, particularly cerebral ischemia, is critical for improving overall outcomes. Cerebral oximetry, which measures regional cerebral oxygen saturation (rSO2 ) by near‐infrared spectroscopy, has emerged as a potentially beneficial marker of cerebral ischemia during CPR. In numerous preclinical and clinical studies, higher rSO2 during CPR has been associated with improved cardiac arrest survival and neurologic outcome. In this narrative review, we summarize the scientific rationale and validation of cerebral oximetry across populations and pathophysiologic states, discuss the evidence surrounding its use to predict return of spontaneous circulation, rearrest, and neurologic outcome, and provide suggestions for incorporation of cerebral oximetry into CPR practice.